Two‐Dimensional Silicene–Stanene Heterostructures by Epitaxy. (19th May 2021) - Dhungana, Daya Sagar; Grazianetti, Carlo; Martella, Christian; Achilli, Simona; Fratesi, Guido; Molle, Alessandro
Abstract: The synthesis of new Xenes and their potential applications prototypes have achieved significant milestones so far. However, to date the realization of Xene heterostructures in analogy with the well known van der Waals heterostructures remains an unresolved issue. Here, a Xene heterostructure concept based on the epitaxial combination of silicene and stanene on Ag(111) is introduced, and how one Xene layer enables another Xene layer of a different nature to grow on top is demonstrated. Single‐phase (4 × 4) silicene is synthesized using stanene as a template, and stanene is grown on top of silicene on the other way around. In both heterostructures, in situ and ex situ probes confirm layer‐by‐layer growth without intercalations and intermixing. Modeling via density functional theory shows that the atomic layers in the heterostructures are strongly interacting, and hexagonal symmetry conservation in each individual layer is sequence selective. The results provide a substantial step toward currently missing Xene heterostructures and may inspire new paths for atomic‐scale materials engineering. Abstract : Two Xene heterostructures based on two well‐established configurations, silicene‐on‐Ag(111) and stanene‐on‐Ag(111), are presented. Various in situ and ex situ analysis, along with theoretical studies, confirm that one Xene layer can act as a suitable template for the other reciprocal Xene layer. This demonstration of the Xene heterostructure opens a door to a new atomic‐scale materials engineering.